INSTRUMENTALITY OF WOMEN IN DAMSEL MOVIE (2024) - Yosep Liderman Panggabean; Mike Wijaya Saragih (Prodi Sastra Inggris UKI, 2024)
In the film Damsel (2024), directed by Juan Carlos Fresnadillo, the traditional damsel in distress narrative is subverted by the character of Princess Elodie, who transforms from a passive pawn to an empowered individual. The film critiques societal structures that objectify women by exploring Elodie’s journey from being a tool in an arranged marriage and a sacrificial victim to confronting a dragon. This study aims to explore how the film portrays the instrumentalization of Elodie through qualitative descriptive methods, grounded in Nussbaum's theory of objectification, particularly the concept of instrumentality. As the result, the study identifies three forms of Elodie's instrumentalization: subjected to an arranged marriage, subjected to a life sacrifice, and subjected to a target for revenge. From these three forms of Elodie's instrumentalization, this film shows Elodie's gradual assertion of autonomy and rejection of the roles assigned to her, deconstructing conventional girl tropes and highlighting the broader implications of challenging patriarchal norms. The finding of the instrumentalization of Elodie in the film Damsel is shown to become more complex along with the resistance carried out to oppose the prevailing patriarchal norms.